Nudging down theft from insecure vehicles. A pilot study - Roach, Jason (International journal of police science & management, 2017)
This report presents the preliminary findings of a pilot study to reduce thefts from cars committed against insecure vehicles, using the behavioural insights or ‘nudge approach’. The recipients of the ‘nudges’ were potential victims of theft from insecure vehicles living in high rate areas for this crime, where a bespoke leaflet campaign was developed to nudge vehicle owners into thinking more carefully when leaving their vehicles unattended, particularly when left on their driveways overnight. Although somewhat tentative at this stage, the preliminary findings indicate that the percentage of thefts committed against insecure vehicles in the two treatment areas was reduced significantly when compared with the two control group areas where no nudge interventions were introduced. This demonstrates that if appropriate nudges (grounded in psychological theory) are coupled with and delivered by appropriate messengers, the prosocial behavioural change can be encouraged which can lead to a reduction in criminal behaviour and opportunities for crime.